Multimedia Based E-Learning Development for The Effectiveness of Distance Learning - Didik Himmawan; Nur Izzatun Fauzi; Nanang Priono (Konsultan Jurnal Ilmiah Indonesia, 2025)
E-Learning is a distance learning process that combines the principles of the learning process with technology, as well as a learning system that is used as a means for the instructing and learning handle which is carried out without having to meet confront to confront between instructors and understudies. In this inquire about we attempt to create multimedia-based e-learning and degree the adequacy of learning results by applying interactive media to e-learning. The concept of multimedia is a combination of two or more media elements consisting of text, images, photos, audio, video and animation in an integrated manner, The quality of student learning can be improved and the teaching and learning process can be carried out anywhere and at any time, as well as students' learning attitudes can be improved. Learning content is the most important thing in the teaching and learning process, in distance learning, content must receive important attention, because in distance learning Far from it, learning participants get a greater proportion of the material from reading content independently rather than from face-to-face with the teacher. The type of research method is a library study approach, library study is a theoretical study, references and scientific literature related to the theme being observed. The effectiveness of distance learning can mean measuring the success of each learning process between students and students, or students and teachers to achieve learning goals. The effectiveness of distance learning can be seen from several aspects and supporting factors that influence the effectiveness of distance learning.